Pregnancy outcomes in a malaria-exposed Malian cohort of women of child-bearing age - Gaoussou, Santara; Attaher, Oumar; Swihart, Bruce; Traore, Moussa; Diarra, Soumaila; Soumbounou, Ibrahim H.; Ndiaye, Oulematou; Issiaka, Djibrilla; Morrison, Robert; Mahamar, Almahamoudou; Duffy, Patrick E.; Dicko, Alassane; et al. (Frontiers in Medicine, 2022)
In Sub-Saharan Africa, malaria continues to be associated with adverse pregnancy outcomes including stillbirth, early neonatal death, preterm delivery, and low birth weight. Current preventive measures are insufficient and new interventions are urgently needed. However, before such interventions can be tested in pregnant women, background information on pregnancy outcomes in this target population must be collected. We conducted an observational study in Ouélessébougou, Mali, a malaria-endemic area where first antenatal visit commonly occurs during the second trimester of pregnancy, hindering calculation of miscarriage rate in the population. To accurately determine the rate of miscarriage, 799 non-pregnant women of child-bearing age were enrolled and surveyed via monthly follow up visits that included pregnancy tests. Out of 505 women that completed the study, 364 became pregnant and 358 pregnancies were analyzed: 43 (12%) resulted in miscarriage, 28 (65.1%) occurred during the first trimester of pregnancy. We also determined rates of stillbirth, neonatal death, preterm delivery, and small for gestational age. The results showed high rate of miscarriage during the first trimester and established a basis to evaluate new interventions to prevent pregnancy malaria. This survey design enabled identification of first trimester miscarriages that are often missed by studies conducted in antenatal clinics. Clinical trial registration [https://clinicaltrials.gov/], identifier [NCT0297 4608].